2023
DOI: 10.3389/fmed.2023.1089361
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for skin carcinomas: A systematic review and meta-analysis

Abstract: BackgroundPhotodynamic therapy (PDT) is increasingly used for the treatment of basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). However, it is unknown whether photodynamic therapy is more effective than other commonly used treatment modalities for these cancers.PurposeThe aim of this study was to determine the relative efficacy and safety of PDT compared with placebo or other interventions for the treatment of skin carcinomas.MethodsSearches were performed in PubMed, Web of Science, Embase, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Successful use of PDT for BCC, SCC, and SCCIS has been documented in the literature. 5 , 10 Our retrospective case series similarly reports 10 cases of NMSC that resolved with an average of 2 sessions of blue light PDT with 10% ALA gel and range of 1 to 4 sessions. Notably, no evidence of recurrence occurred at > 5 years after the final treatment session.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Successful use of PDT for BCC, SCC, and SCCIS has been documented in the literature. 5 , 10 Our retrospective case series similarly reports 10 cases of NMSC that resolved with an average of 2 sessions of blue light PDT with 10% ALA gel and range of 1 to 4 sessions. Notably, no evidence of recurrence occurred at > 5 years after the final treatment session.…”
Section: Discussionmentioning
confidence: 87%
“…A meta-analysis of 17 unique randomized controlled trials (RCTs) of PDT for BCCs and SCCs in adults showed that PDT was more likely to receive a “good” or “excellent” rating for cosmetic outcome than surgery or cryotherapy. 5 PDT may therefore offer a good option for NMSC lesions on the face or other cosmetically sensitive locations. Additionally, PDT has been studied extensively as an effective field cancerization therapy for AKs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This then induces a reaction within the cell, causing toxic singlet oxygen species to form locally, resulting in the cell's death. 5 PDT is used and being investigated as a targeted and minimally invasive treatment option for many areas of oncology such as for skin, 6 head and neck, 7 bladder, 8 lung, 9 and esophageal cancers. 10 There are several clinical trials, past, present, and future, aiming to explore the potential of PDT for GBM treatment.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Furthermore, PDT remains effective for tumor recurrence after radiotherapy and chemotherapy, delivering remarkable therapeutic outcomes. [56,57] PDT operates through the photosensitization reaction with the involvement of oxygen molecules and biological effects. Upon laser irradiation with a specific wavelength, the photosensitizer absorbs energy and then transfers it to the surrounding oxygen molecules.…”
Section: Pdtmentioning
confidence: 99%